Poor health, unhealthy behaviors, and unfavorable work characteristics influence pathways of exit from paid employment among older workers in Europe: a four year follow-up study - Suzan JW Robroek; Merel Schuring; Simone Croezen; Mikael Stattin; Alex Burdorf (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: The aim of this study was to get insight into the role of poor health, unhealthy behaviors, and unfavorable work characteristics on exit from paid employment due to disability pension, unemployment, and early retirement among older workers. METHODS: Respondents of the longitudinal Survey of Health, Ageing, and Retirement in Europe (SHARE) in 11 European countries were selected when (i) aged between 50 years and the country-specific retirement age, (ii) in paid employment at baseline, and (iii) having information on employment status during the 4-year follow-up period (N=4923). Self-perceived health, health behaviors, and physical and psychosocial work characteristics were measured by interview at baseline. Employment status was derived from follow-up interviews after two and four years. Cox proportional hazards regression analyses were used to identify determinants of unemployment, disability pension, and early retirement. RESULTS: Poor health was a risk factor for disability pension [hazard ratio (HR) 3.90, 95% confidence interval (95% CI) 2.51-6.05], and a lack of physical activity was a risk factor for disability pension (HR 3.05, 95% CI 1.68-5.55) and unemployment (HR 1.84, 95% CI 1.13-3.01). A lack of job control was a risk factor for disability pension, unemployment, and early retirement (HR 1.30-1.77). CONCLUSIONS: Poor health, a lack of physical activity, and a lack of job control played a role in exit from paid employment, but their relative importance differed by pathway of labor force exit. Primary preventive interventions focusing on promoting physical activity as well as increasing job control may contribute to reducing premature exit from paid employment.